(untitled) (International Seven Journal of Multidisciplinary, 2023)
Over time, several changes end up taking place in human societies, influenced by the most varied factors. The job market is a good example of such a phenomenon, where transformations have the power to profoundly impact an individual’s life. Although such transformations often occur quickly, influenced by technological developments, some aspects end up undergoing changes considerably more slowly, one of them being the paradigms connected to female work, paradigms that end up presenting considerable difficulties and dilemmas to women who are part of the process. or intend to integrate the labor market. Therefore, the present work aimed to identify the difficulties and problems faced by women in the labor market, using a combination of theoretical and practical methods. Initially, a systematic survey was carried out on the subject, using various bibliographic sources, available in physical and digital media. Subsequently, seeking to deepen the study, a questionnaire was applied, focusing on the knowledge of the respondents’ view on the relationship of women with the labor market, based on their experiences and perceptions. At the end of the study, it was possible to identify that the information collected during the bibliographic research coincides with the perception of the respondents of the questionnaire, where although the way women are seen and treated in the labor market has improved, there is still a long way to go. traveled for a state of true equality to be reached. DOI: 10.56238/isevmjv1n2-007